The Exeter V40 cemented femoral component at a minimum 10-year follow-up: the first 540 cases. (August 2018) - Westerman, R. W.; Whitehouse, S. L.; Hubble, M. J. W.; Timperley, A. J.; Howell, J. R.; Wilson, M. J.
Abstract : Aims: The aim of this study was to report the initial results of the Exeter V40 stem, which became available in 2000. Patients and Methods: A total of 540 total hip arthroplasties (THAs) were performed in our unit using this stem between December 2000 and May 2002. Our routine protocol is to review patients postoperatively and at one, five, and ten years following surgery. Results: A total of 145 patients (26.9%) died before ten years and of the remaining 395 stems, 374 (94.7%) remain in situ . A total of 21 well-fixed stems (5.3%) were revised. Ten were exchanged using a cement-in-cement technique to facilitate acetabular revision. Three were revised for infection, one for instability, one for fracture of the stem, and six following a periprosthetic fracture. An additional 16 acetabular components (4.1%) were revised; five for aseptic loosening and 11 for instability. There were no revisions for aseptic loosening of the stem, and no evidence of aseptic loosening in any hip. The fate of every stem is known and all patients remain under review. Survivorship, with revision of the stem for aseptic loosening as the endpoint, was 100%. At 13.5 years, the Kaplan–Meier survival rate for all-cause revision of the stem was 96.8% (95% confidence interval (CI) 94.8 to 98.8) and all-cause revision (including acetabular revision, infection, and instability) was 91.2% (95% CI 88.3 to 94.1). Conclusion: No stem was revised for aseptic loosening in this series. The contemporary Exeter V40 stem continues to perform well, and survival has remained comparable with that of the Exeter Universal stem. Cite this article: Bone Joint J 2018;100-B:1002–9.